Shape parameters of UGV delivery robots that affect subject's perception of safety - da Silva, Vithor Hugo Costa; Masuko, Soh; Bao, Suomiya; Yamanaka, Toshimasa (2022 10th International Conference on Affective Computing and Intelligent Interaction Workshops and Demos (ACIIW), 2022)
When developing new technologies, the safety of people is always important. Mostly, this is assured by safety standards that are also developed in the same direction as technologies. However, from a psychological perspective, it is also essential to investigate whether people feel safe under certain circumstances. The goal of this study was to find out what kind of appearance and shape parameters could affect the feeling of safety. It was evaluated 32 different designs of delivery UGV (unmanned ground vehicles) robots developed by different companies worldwide to conclude which shape factors have a positive or negative impact on perceived safety. This report presents some of the findings already identified in the study. The results show that for Brazilian subjects the robot's forward slant shape, backward slant shape, and roundness are shape factors that may influence on safety feeling. Additionally, nationality may play significant differences in the perception of safety towards the shape of a delivery UGV robot. Those findings are important to deepen the discussion in the effect of shape as a fundamental visual aspect on robot's design, and how far they can be related to the feeling of safety, which is primordial for a better acceptance of robots in social environment. Finally, further work is mentioned as a plan for the next steps of this study.